2022
DOI: 10.1186/s13195-022-01027-2
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated reactions to learning Alzheimer’s disease biomarker results

Abstract: Introduction We developed the Alzheimer’s Biomarker Survey to assess willingness to enroll in biomarker studies that disclose results and anticipated reactions to an elevated biomarker result. Methods Participants included cognitively unimpaired adults enrolled in longitudinal AD studies (n = 334, mean age = 64.8 ± 7.7, 44% non-Hispanic Black or African American). Exploratory and confirmatory factor analyses determined the latent structure comprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…The survey included measures assessing experience with and concern about AD, 9 perceived health, health locus of control (LOC), 10 brain health social norms, 11 research attitudes, 12 and chronic experiences of perceived discrimination due to race, ethnicity, self-identified sex, age, or other interpersonal characteristics 13 . We previously reported that results of exploratory and confirmatory factor analysis revealed an underlying factor structure comprising 14 items assessing anticipated psychological impact (3 factors: distress, stigma, cognitive symptoms) and 14 items assessing anticipated behavior change (2 factors: planning, dementia risk-reduction) associated with learning AD biomarker results and confirmed measurement invariance across White and Black or African American participants in our cohort 4 . These 28 items were either adapted from existing questionnaires 14,15 or developed by the study team.…”
Section: Methodssupporting
confidence: 82%
See 2 more Smart Citations
“…The survey included measures assessing experience with and concern about AD, 9 perceived health, health locus of control (LOC), 10 brain health social norms, 11 research attitudes, 12 and chronic experiences of perceived discrimination due to race, ethnicity, self-identified sex, age, or other interpersonal characteristics 13 . We previously reported that results of exploratory and confirmatory factor analysis revealed an underlying factor structure comprising 14 items assessing anticipated psychological impact (3 factors: distress, stigma, cognitive symptoms) and 14 items assessing anticipated behavior change (2 factors: planning, dementia risk-reduction) associated with learning AD biomarker results and confirmed measurement invariance across White and Black or African American participants in our cohort 4 . These 28 items were either adapted from existing questionnaires 14,15 or developed by the study team.…”
Section: Methodssupporting
confidence: 82%
“…13 We previously reported that results of exploratory and confirmatory factor analysis revealed an underlying factor structure comprising 14 items assessing anticipated psychological impact (3 factors: distress, stigma, cognitive symptoms) and 14 items assessing anticipated behavior change (2 factors: planning, dementia risk-reduction) associated with learning AD biomarker results and confirmed measurement invariance across White and Black or African American participants in our cohort. 4 These 28 items were either adapted from existing questionnaires 14,15 or developed by the study team. For 8 items, participants were asked to rate the importance of each item as a reason to learn their biomarker results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…About one-third of our participants who stated they were already hesitant about research indicated they were worried or uncertain about being given abnormal test results. This aligns with researchers’ concerns about causing psychological harm or creating uncertainty about what the meaning of results – particularly with asymptomatic individuals [15, 16, 3235]. Future research is needed to determine how to ethically and meaningfully return results to participants, particularly those from diverse populations.…”
Section: Discussionmentioning
confidence: 92%
“…Several drafts were reviewed by the study team, Survey Center, and external content expert consultants. The ABS has been found to be a reliable and validated measure of anticipated reactions when communicating AD biomarker results to research participants, 25 and results about the willingness to enroll in biomarker studies have been previously described. 26 To assess willingness to share biomarker results, we used a vignette describing a hypothetical AD biomarker study (see Table 1).…”
Section: Surveymentioning
confidence: 99%